2017
DOI: 10.1038/s41598-017-08035-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete alanine scanning of the Escherichia coli RbsB ribose binding protein reveals residues important for chemoreceptor signaling and periplasmic abundance

Abstract: The Escherichia coli RbsB ribose binding protein has been used as a scaffold for predicting new ligand binding functions through in silico modeling, yet with limited success and reproducibility. In order to possibly improve the success of predictive modeling on RbsB, we study here the influence of individual residues on RbsB-mediated signaling in a near complete library of alanine-substituted RbsB mutants. Among a total of 232 tested mutants, we found 10 which no longer activated GFPmut2 reporter expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…σ E activation is triggered by various stress signals, which are sensed in the cellular envelope and communicated to the cytoplasmic compartment by a complex signal transduction pathway [25]. rbsB is a periplasmic ribose-binding protein involved in the ATP-dependent ribose uptake [26].…”
Section: E Coli Proteome Response To Challenge By Chitosanmentioning
confidence: 99%
“…σ E activation is triggered by various stress signals, which are sensed in the cellular envelope and communicated to the cytoplasmic compartment by a complex signal transduction pathway [25]. rbsB is a periplasmic ribose-binding protein involved in the ATP-dependent ribose uptake [26].…”
Section: E Coli Proteome Response To Challenge By Chitosanmentioning
confidence: 99%
“…Detecting and separating mutants from the initial library with such small improvement of inducibility by 13CHD required optimization of the screening method. We initially screened the library for gain-of-fluorescence upon induction on individual cells, but found that single cell variation was too high and resulted in many false-positive signals 30 . Instead, therefore, we switched to growing reporter cells inside alginate beads to microcolonies, which improved the reproducibility and screening efficiency, and reduced the number of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…In the final computational strategy we stripped the presumed RbsB binding pocket at nine positions (changing virtually to Ala-residues), sampled the positions for 13CHD and CH with the lowest ΔG, and predicted the sets of amino acid residues to contribute with improved 13CHD and CH binding. Although this seemed the best strategy at the time, a more recent and complete Ala-substitution screening of RbsB by our group found four crucial residues for ribose recognition (D89, N190, D215, R141) 13 , two of which (D215, R141) were not included in the library predictions. In contrast, that study found several residues critical for RbsB folding and/or translocation, notably D89 and N190, which were targeted here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent engineering of the most sensitive published RbsB mutant (named TNT.R3), however, failed to reproduce the reported TNT detection at sub–µM concentrations in the E. coli Trz1-OmpR background and also failed to demonstrate TNT binding by a purifed TNT.R3 mutant using in vitro microcalorimetry 12 . Subsequent analysis of effects of alanine-substitutions in wild-type E. coli RbsB showed that mutations at 12 positions result in misfolded or poorly translocated proteins, one of which was also targeted in the TNT.R3 variant 13 . Purification and biophysical analysis of a further set of published mutant PBPs also failed to reproduce the original measurements, and suggested the cause being their misfolding and unintended oligomerization 14 .…”
Section: Introductionmentioning
confidence: 99%